PENGAWASAN PERIZINAN OLEH KOMISI PENYIARAN INDONESIA DAERAH (KPID) PROPINSI BANTEN UNTUK TV SWASTA LOKAL - ANDRIANSYAH ANDRIANSYAH; TAUFIQUROKHMAN TAUFIQUROKHMAN; EVI SATISPI (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2018)
Licensing is the main thing about broadcasting arrangements. In a series of broadcasting regulatory process stages, licensing becomes the decision stage of the state (through KPI and KPID) to provide an evaluation (evaluation) whether a broadcasting agency is eligible to be granted or eligible to continue lease rights over the frequency.Indonesia Regional Broadcasting Commission or KPID is an independent state institution in Indonesia established in each province functioning as a regulator of broadcasting in every province in Indonesia. KPID is an institution capable of controlling the media, especially concerning Broadcasting Permit.License of Broadcasting (IPP) is the right granted by KPID to broadcasters to conduct broadcasting. To date there are seven local private television broadcasters in Banten Province (1.Untirta TV; 2. Baraya TV; 3. CTV Banten; 4. TV3 Tangerang; 5. CCNC; 6. Carlita TV; 7. CTV Network) broadcasting to obtain broadcasting licenses.The results of the study said that in the level of requirements that must be met by local private television broadcasters to obtain IPP, KPID has performed its duties optimally. KPID is always proactive towards local private television broadcasting institutions especially in guiding to complete the necessary conditions so that local TV in Banten Province can meet the requirements needed to manage IPP.However, in the implementation of its role related to the phases of acquisition of IPP, KPID has not played an optimal role in performing its duties and functions. This is because in broadcasting there is still a violation by local private TV in broadcasting concerning the content of the broadcasting. In addition, in taking the policy, KPID is still intervened by the local government in the form of broadcast television broadcasting that is in accordance with local government requests, which KPID should not be interfered by any party considering KPID is an independent institution. So it can be concluded that KPID in general can not perform its duties and functions properly. Kata kunci: KPID, Licensing, and Broadcasting Operating License